Contemporary sculptors - Kracun, Danijela (Atglen, PA Schiffer Pub. Limited, 2012)
An eclectic group of 84 international artists guide us on a journey of beauty and art through 477 inspiring sculptures. Enjoy the variety of sculptures from the traditional to the avant garde, the serious to the whimsical. Artists employ a variety of media, including bronze, clay, glass, stone, and wood, as well as some less common materials such as ice, sand, and even food. The diversity of the their work and the range of their creativity and resourcefulness provides insight into the international trends in art today. The result is an eye-catching and wonderfully informative look at contemporary art. A must-have reference for serious art collectors and enthusiasts.
Keywords: Sculpture, Modern -- 21st century; Sculpture, Modern -- Pictorial works; Sculptors -- Biography; Modernism (Art).